Emotional attachment and resistance to change in the use of technology: A study among Chinese university music teachers - Juanjuan Wang; Fang Huang; Timothy Teo (PLoS ONE, 2025)
While technology adoption has received widespread attention in teaching, little research has been conducted on the impact of emotional attachment and resistance to change on technology adoption by teachers, especially in the field of music. This study adopted an extended technology acceptance model to examine music teachers’ technology adoption in the context of Chinese university teaching. These results suggest that music teachers in the Chinese universities have positive attitudes toward the use of technology in music education. Their technology using intention was based significantly on the perceived usefulness, their own attitudes toward technology, emotional attachment, and resistance to change. These variables explain 89% of the variance in music teachers’ technology adoption intention. Additionally, music teachers’ emotional attachment related considerably to the perceived usefulness of technology and resistance to change which proved to be a significant precursor to perceived ease of use. Pedagogical suggestions are provided to improve design thinking and technology adoption for music teachers.